Gender mainstreaming: A study of efforts by the UNDP, the world bank and the ILO to institutionalize gender issues - Carol Miller; Shahra Razavi (United Nations Research Institute for Social Development (UNRISD), 1995)
The Fourth World Conference on Women, held in Beijing in September 1995, provided an opportunity for the world community to focus attention on areas of critical concern for women worldwide - concerns that stem from social problems embracing both men and women, and that require solutions affecting both genders. One of the main objectives of the Conference was to adopt a platform for action, concentrating on some of the key areas identified as obstacles to the advancement of women. UNRISD's work in preparation for the Fourth World Conference on Women focused on two of the themes highlighted by the United Nations Commission on the Status of Women: inequality in women's access to and participation in the definition of economic structures and policies and the productive process itself; and insufficient institutional mechanisms to promote the advancement of women. The Institute's Occasional Paper series for Beijing reflects work carried out under the UNRISD/UNDP project, Technical Co-operation and Women's Lives: Integrating Gender into Development Policy. The activities of the project include an assessment of efforts by a selected number of donor agencies and governments to integrate gender issues into their activities; the action-oriented part of the project involves pilot studies in Bangladesh, Jamaica, Morocco, Uganda and Viet Nam, the goal of which is to initiate a policy dialogue between gender researchers, policy makers and activists aimed at making economic policies and productive processes more accountable to women. This paper takes up the first activity mentioned above by providing an account of efforts to mainstream gender in the UNDP, the World Bank and the ILO. It identifies some of the obstacles that have been encountered in the different institutional settings and highlights the opportunities for further progress.
Keywords: 330